PORTRAYING STUDENTS’ SPEAKING FOREIGN LANGUAGE ANXIETY LEVEL DURING THE ONLINE LEARNING AND REVEALING THE USE OF PAIR GROUP WORK STRATEGY TO DECREASE THE STUDENTS’ SPEAKING FOREIGN LANGUAGE ANXIETY IN OFFLINE LEARNING - Eka Pratiwi Yunianti; Arif Alexander Bastian; Dyah Fitri Mulati; Defy Gustianing; Septika Ariyanti (IKIP Siliwangi, 2023)
The goals of the current study were to describe the students' degree of speaking anxiety while learning a foreign language online and to demonstrate how pair group work was used to reduce speaking anxiety when learning a language offline. 28 students from Universitas Aisyah Pringsewu were among the participants in this study. This study used a descriptive qualitative research approach. A speaking foreign language anxiety questionnaire that was adapted from Ozturk was used to gather the data (2014). The survey form used a 5-graded likert scale, and the data were analyzed by categorizing the findings in accordance with guidelines adapted from Ozturk's range levels (2014). The majority of students had moderate levels of speaking anxiety, and there were also a small number of students with high levels of speaking anxiety, according to the results of a pre- and post-test. However, after using a pair-group work strategy, no students were found to have high levels of speaking anxiety. In light of this, it can be said that the pair-group work technique has a positive effect on the students' anxiety related to speaking a foreign language. Keywords: Foreign Language Speaking Anxiety; Pair Group Work Strategy; Online and Offline Learning